Peran Bimbingan Konseling Bagi Anak Tunagrahita Dalam Interaksi Sosial Di Sekolah Luar Biasa Pertiwi Ponorogo - Azam Jundullah; Alfi Farhati; Muh. Febri Syihab Azzuhri (IKTIFAK: Journal of Child and Gender Studies, 2023)
The Role of Counseling Guidance for Mentally Disabled Children in Social Interactions at SLB Pertiwi Ponorogo Academic Year 2022/2023 Counseling Guidance is assistance provided by counselors to individuals face to face so that they are able to solve the problems they have and are able to find their own value and be able to become a better person than before . Mental retardation is a condition of children whose intelligence level is below average, characterized by limited intelligence and incompetence in social communication. Children with mental retardation have difficulties in social interaction due to underdeveloped social factors as a result of obstacles in their intellectual aspect. The formulation of the problem in this research is (1) How is counseling carried out for mildly mentally retarded children in social interactions at SLB Pertiwi Ponorogo? (2) What are the factors inhibiting light tuagahita children in social interactions? (3) What is the role of counseling guidance for children with mild mental retardation in social interactions? This research aims to (1) To determine the implementation of counseling guidance for mentally retarded children at the Pertiwi Ponorogo Special School. (2) To determine the inhibiting factors for mentally retarded children in social interactions at the Pertiwi Ponorogo Special School. (3) To determine the role of counseling guidance for mentally retarded children in social interaction at the Pertiwi Ponorogo Special School. This type of research is field research with a descriptive approach, which means that data is obtained through research objects using data collection techniques. Data is obtained from research objects using data collection techniques to be analyzed based on existing theories in order to understand the role of counseling for mentally retarded children in interactions. social at SLB Pertiwi Ponorogo. This research produces the following conclusions: (1) The implementation of counseling guidance at SLB Pertiwi Ponorogo is carried out by homeroom teachers who have coordinators to mobilize and control counseling guidance activities because there are no counselors or teachers with counseling guidance qualifications. (2) Inhibiting factors for mentally retarded children in social interaction, namely the difficulty of mentally retarded children in communicating and making social contacts, this is due to the low intelligence abilities and social development of mentally retarded children. (3) The role of counseling guidance for mildly mentally retarded children in social interactions at the Pertiwi Ponorogo SLB is to help mildly mentally retarded children solve their problems and help improve the skills and self-independence of mildly mentally retarded children.